Built-up procedure in managing air cargo at MASkargo KLIA / Khairul Azly Ramly - Ramly, Khairul Azly (Faculty of Business and Management, 2010)
This study is about built-up procedures managing air cargo at MASkargo KLIA . It consists of introduction which will briefly explain the information on the background of the company, the issue and background of the study. This study will be focus on the built-up procedure managing the cargo by the company. It will briefly discuss about the problem that arise during the procedure used while loading and unloading cargo. The information gathering for this study will be based on an extensive research of the relevant journal, articles, websites including the company websites and related documents about the company handled the built-up procedure. The conclusion of this study was the outcome from the findings. Through the research, it shows based on the clear finding, result that are observed. The finding showed there are a little different between facts and company practice in gap analysis.